Development of Micro-Electrode Array Based Tests for Neurotoxicity: Assessment of Interlaboratory Reproducibility with Neuroactive Chemicals - Novellino, Antonio; Scelfo, Bibiana; Palosaari, Taina; Price, Anna; Sobanski, Tomasz; Shafer, Timothy J.; Johnstone, Andrew F.; Gross, Guenter W.; Gramowski, Alexandra; Schroeder, Olaf; Jügelt, Konstantin; Chiappalone, Michela; et al. (Frontiers in Neuroengineering, 2011)
Neuronal assemblies within the nervous system produce electrical activity that can be recorded in terms of action potential patterns. Such patterns provide a sensitive endpoint to detect effects of a variety of chemical and physical perturbations. They are a function of synaptic changes and do not necessarily involve structural alterations. In vitro neuronal networks (NNs) grown on Micro-Electrode Arrays (MEAs) respond to neuroactive substances as well as the in vivo brain. As such, they constitute a valuable tool for investigating changes in the electrophysiological activity of the neurons in response to chemical exposures. However, the reproducibility of NN responses to chemical exposure has not been systematically documented. To this purpose six independent laboratories (in Europe and in USA) evaluated the response to the same pharmacological compounds (Fluoxetine, Muscimol, and Verapamil) in primary neuronal cultures. Common standardization principles and acceptance criteria for the quality of the cultures have been established to compare the obtained results. These studies involved more than 100 experiments before the final conclusions have been drawn that MEA technology has a potential for standard in vitro neurotoxicity/neuropharmacology evaluation. The obtained results show good intra- and inter-laboratory reproducibility of the responses. The consistent inhibitory effects of the compounds were observed in all the laboratories with the 50% Inhibiting Concentrations (IC50s) ranging from: (mean ± S.E.M., in M) 1.53±0.17 to 5.4±0.7 (n=35) for Fluoxetine, 0.16±0.03 to 0.38±0.16 µM (n=35) for Muscimol, and 2.68±0.32 to 5.23±1.7 (n=32) for Verapamil. The outcome of this study indicates that the MEA approach is a robust tool leading to reproducible results. The future direction will be to extend the set of testing compounds and to propose the MEA approach as a standard screen for identification and prioritization of chemicals with neurotoxicity potential.